Hypnosis and Against Pain Intensity Decrease in Cervical Cancer Patients in the Surgical Ward - Petrus Nugroho DS; Herry Prasetyo; Ulfah Agus Sukrillah (Jurnal LINK, 2012)
Hynosis therapy was developed as a part of independent nursing intervention to release the intense of pain that cervical cancer patients suffer from. Therefore, the goal of this research is to investigate the effect of hypnosis therapy towards decreasing the intense of pain that the patients with cervical cancer in the stage III hospitalized in surgical ward.  The research method was pre and post test design without control group. The intervention was hypnosis therapy that was provided by nurse expert in that field towards cervical cancer patient in the stage III. 6 patients were invited in this study and were provided hypnosis therapy. The measuring pain scale  (0-10) was given before and after the therapy. The research showed that there was decreasing the intense of pain from 6,33 to 5,17 after hynosis therapy. Moreover, the verbal complains also changed from crying to only moan after the therapy.